Measurements of emanation of radon isotopes in residental and administrative buildings - Dyachkov, V.V.; Biyasheva, Z.M.; Ismagulova, D.A.; Nuketay, A.B.; Zaripova, Y.; Shakirov, A.L.; Yushkov, A.V. (Recent Contributions to Physics, 2019)
The distribution of alpha activity of natural radionuclides in boarding schools located near the tectonic fault zones of Almaty was studied. Measurements were made in boarding schools, which are both residential and administrative buildings. As a result of the measurements, a 2D topology of the distribution of the alpha-radiation flux density of radon isotopes and their daughter decay products from the measurement height (number of storeys) for each boarding school was made. In addition, a 2D topology of the distribution of alpha-radiation flux density from the distance to the tectonic fault was compiled. According to the measurement results, the concentration coefficient of radon was found depending on the distance from the tectonic fault. Using the obtained regularity, it is possible to construct a graph of the dependence of volume alpha activity for other schools, if their distance from the tectonic fault is known.